Ecocriticism - Garrard, Greg (The new critical idiom, 2012)
Inspired by a range of ecological movements, ecocriticism explores the ways in which we imagine and portray the relationship between humans and the environment in all areas of cultural production, from Wordsworth and Thoreau to Disney and BBC nature documentaries. Greg Garrard's animated and accessible volume traces the development of the movement and explores the concepts which have most occupied ecocritics, including: * pollution * wilderness * apocalypse * dwelling * animals * earth. Featuring an invaluable glossary of terms and suggestions